An exploration of diabetes self-management among young people with type 2 diabetes mellitus - Othman, Nursyuhadah (2024)
Life-long patient-driven self-management is the cornerstone in mitigating diabetesrelated complications, however, studies showed that diabetes self-management interventions for young people with type 2 diabetes mellitus (T2DM) yielded mixed results in changing behaviours and glycaemic control. Also, information on diabetes self-management practices among young people with T2DM in Malaysia remains scarce. This study aimed to investigate the lived experience of disease management from the perspectives of young patients with T2DM, caregivers and healthcare professionals (HCPs). First, a meta-synthesis was conducted to identify the factors influencing diabetes self-management among young people. A systematic search was conducted using PubMed, Scopus, Web of Science (WoS) and Cumulative Index to Nursing and Allied Health Literature (CINAHL) to identify peer-reviewed articles. Quality appraisal was performed using the Critical Appraisal Skills Programme (CASP). All extracted data underwent thematic analysis using the socio-ecological model as a framework.